Aplikasi seni video sebagai reaksi terhadap propaganda barat - Nur Erna, binti Herman (University Malaysia Sarawak, UNIMAS., 2006)
This art wok is produced by using the application of video as the reaction of west propaganda. The producing of this art wok is type of propaganda which is characterized as a form of global communication in art. This art work shows the issues about the political and war controversy. The purpose of the art work is to convey the war issues that happened in the west